Masculinity and child homicide - Alder, Christine (The British journal of criminology, 1996)
In this article masculinity and violence are explored through an examination of case studies of child homicides committed by men in Victoria, Australia between 1985 and 1994. The findings reveal a diversity of violent scenarios and a complexity in masculinity and its relationship to violence. They challenge the adequacy of universalistic representations of male violence as either an instrumental act, a means of accomplishing masculinity, or as an unpremenditated emotional act of rage and anger in response to a threat. In particular, the scenarios reveal both the complex and sometimes contradictory expectations of masculinities and the ways in which they are achieved differently in different situations